Harmonising research outcomes for polycystic ovary syndrome: an international multi-stakeholder core outcome set. Issue 2 (4th February 2020) - Al Wattar, Bassel H; Teede, Helena; Garad, Rhonda; Franks, Steve; Balen, Adam; Bhide, Priya; Piltonen, Terhi; Romualdi, Daniela; Laven, Joop; Thondan, Mala; Bueno-Cavanillas, Aurora; Moss, Ngawai; et al.
Abstract: STUDY QUESTION: What are the key core outcomes to be reported in studies on polycystic ovary syndrome (PCOS)? SUMMARY ANSWER: We identified 3 generic and 30 specific core outcomes in 6 specialist domains: metabolic (8), reproductive (7), pregnancy (10), oncological (1), psychological (1) and long-term outcomes (1). WHAT IS KNOWN ALREADY: Research reporting PCOS is heterogeneous with high variation in outcome selection, definition and quality. STUDY DESIGN, SIZE, DURATION: Evidence synthesis and a modified Delphi method with e-surveys were used as well as a consultation meeting. PARTICIPANTS/MATERIALS, SETTING, METHODS: Overall, 71 health professionals and 123 lay consumers (women with lived experience of PCOS and members of advocacy and peer support groups) from 17 high-, middle- and low-income countries were involved in this analysis. MAIN RESULTS AND THE ROLE OF CHANCE: The final core outcome set included 3 generic outcomes (BMI, quality of life, treatment satisfaction) that are applicable to all studies on women with PCOS and 30 specific outcomes that were categorised into six specialist domains: 8 metabolic outcomes (waist circumference, type 2 diabetes, insulin resistance, impaired glucose tolerance, hypertension, coronary heart disease, lipid profile, venous thromboembolic disease); 7 reproductive outcomes [viable pregnancy (confirmed by ultrasound including singleton, twins and higher multiples), clinical and biochemical hyperandrogenism, menstrual regularity, reproductive hormonal profile, chronic anovulation, ovulation stimulation success including the number of stimulated follicles ≥ 12 mm, incidence and severity of ovarian hyperstimulation syndrome]; 10 pregnancy outcomes (live birth, miscarriage, stillbirth, neonatal mortality, gestational weight gain, gestational diabetes, preterm birth, hypertensive disease in pregnancy, baby birth weight, major congenital abnormalities); 3 psychological outcomes (depression, anxiety, eating disorders); 1 oncological (abnormal endometrial proliferation including atypical endometrial hyperplasia and endometrial cancer); and 1 outcome in the long-term domain (long-term offspring metabolic and developmental outcomes). LIMITATIONS, REASONS FOR CAUTION: We involved lay consumers in all stages of study through e-surveys but not through focus groups, thereby limiting our understanding of their choices. We did not address the variations in the definitions and measurement tools for some of the core outcomes. WIDER IMPLICATIONS OF THE FINDINGS: Implementing this core outcome set in future studies on women with PCOS will improve the quality of reporting and aid evidence synthesis. STUDY FUNDING/COMPETING INTEREST(S): Evidence synthesis was funded through the Australian government, National Health and Medical Research Council (NHMRC) Centre for Research Excellence in PCOS, and H.T. is funded through an NHMRC fellowship. B.H.A. is funded through an NIHR lectureship. All authors have no competing interest to declare.